Buprenorphine/naloxone induction for treatment of acute on chronic pain using a micro-dosing regimen: A case report. Issue 1 (1st January 2019) - Sandhu, Raman; Zivanovic, Rebecca; Klaire, Sukhpreet; Nikoo, Mohammadali; Rozylo, Jennifer; Azar, Pouya
ABSTRACT: Background: Due to its unique pharmacologic properties, efficacy as an analgesic, and role as a first-line medication for the treatment of opioid use disorder, sublingual buprenorphine has emerged as a treatment for patients with concurrent chronic pain and opioid use disorders. One challenge to utilizing buprenorphine is that precipitated opioid withdrawal can result if this medication is initiated in the presence of other opiates with lesser binding affinities. Micro-dosing induction regimens utilize a slower titration to avoid the need for a period of abstinence from other opiates and decrease the risk of precipitated withdrawal. Aims: The aim of this article is to present a case where a standardized micro-dosing induction regimen was used to transition a patient from other opiate analgesia to a sublingual formulation of buprenorphine/naloxone. Methods: This case took place on an inpatient neurosurgical unit of a Canadian tertiary-care city hospital. Written informed consent was collected prior to a detailed chart review. Results: Here we present a case of a postoperative neurosurgical inpatient who was referred to our team for pain management in the context of chronic pain and a past history of opioid use disorder. She was successfully transitioned to buprenorphine/naloxone, replacing all other opioid analgesia, without a period of opioid withdrawal using a micro-dosing induction regimen. Conclusions: Sublingual buprenorphine/naloxone can be safe and effective for treatment of chronic pain, particularly for those with past or current opioid use disorder. Micro-dosing provides a preferable induction strategy for patients who are not able to tolerate the requirement for moderate opioid withdrawal prior to initiation with existing regimens.